1996
DOI: 10.1016/0895-7061(96)00056-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing medication adherence by pill count and electronic monitoring in the African American Study of Kidney Disease and hypertension (AASK) pilot study

Abstract: The Medication Event Monitoring System (MEMS), an electronic monitor which records the date and time of bottle cap openings, and pill counts were used to assess patterns of adherence for the primary antihypertensive drug in the African American Study of Kidney Disease and Hypertension Pilot Study (AASK). Blacks with hypertension and moderately reduced renal function were randomized to one of two levels of blood pressure control and to one of three antihypertensive drug regimens: primary therapy with a calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 25 publications
3
103
0
2
Order By: Relevance
“…15 Prescription fill rate may be more accurate than self-reported adherence, but it is time consuming to track, and information may not be accurate if the patients are not in an integrated health care system or fill prescriptions but do not take the dispensed medication. Pill count is also time-consuming and accurate in determining adherence only in 50%-70% of patients when compared with electronic pillbox 16,17 and 68% when compared with therapeutic drug monitoring. 18 More detailed self-reported questionnaires have been developed to detect medication non-adherence and avoid patients' tendency to report yes when they are simply asked if they have taken medications as prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…15 Prescription fill rate may be more accurate than self-reported adherence, but it is time consuming to track, and information may not be accurate if the patients are not in an integrated health care system or fill prescriptions but do not take the dispensed medication. Pill count is also time-consuming and accurate in determining adherence only in 50%-70% of patients when compared with electronic pillbox 16,17 and 68% when compared with therapeutic drug monitoring. 18 More detailed self-reported questionnaires have been developed to detect medication non-adherence and avoid patients' tendency to report yes when they are simply asked if they have taken medications as prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that adherence to once-daily antihypertensive medication was higher (84%) than to thrice-daily dosing (59%) among 105 hypertensive patients. Similarly, Lee et al (1996) found that African American patients in the AASK cohort, being followed for hypertension and kidney disease, were more adherent to once per day than twice per day regimens measured by electronic monitoring (49% vs. 5% adherence, P < .001).…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…Moreover, based on the existing research, the number of concurrent medications may contribute to adherence or non-adherence. Three of the seven included studies in this area (Dunbar-Jacob et al 2003;Eisen et al 1990;Lee et al 1996) used electronic monitoring to measure adherence.…”
Section: Hypertension and Cardiovascular Diseasementioning
confidence: 99%
“…At present, measurement of adherence in studies of osteoporosis relies mostly on pill counts and selfreporting [43]. Pill counts and self-reporting overestimate true compliance [44][45][46][47][48][49]. In addition, they provide no information on the patient's behaviour surrounding drug intake.…”
Section: How To Investigate Adherencementioning
confidence: 99%